Improving the Chemical Properties of Libyan Cement by Waste Glass Incorporation - Jmal Alfeluo,; Abdelrazag Aziz,; Khaled Aljfairi,; Seraj Aldeeb,; Abdelmoez Aldubouss,; Abdulhamed Ikrieam, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study is concerned with the recycling of colorless glass waste (produced from crushing the glass waste). Prepared in the form of a powder and used as an alternative to cement. The addition of glass powder improved the chemistry of Portland Libyan cement. It is suitable for various applications, such as the cementing process for oil wells. Chemical analysis of a sample of Libyan Portland cement originating from the Libda Cement Factory in Alkhoms city and the Union Cement Factory in Zliten city. The glass powder was mixed and analyzed with Libda and Union cement samples at a ratio (1%, 2%, 4%, 8%, 16%) from the weight of cement. That result was compared to the blank sample result for Libda and Union Cement. Good results are obtained by enhancing the chemical properties of Libda and Union cement. Cement resistance to sulfates was studied for prepared Libda cement samples. The results show that sulfate resistance increases as the percentage weight of glass powder increases relative to the control sample. Sulphate strength was investigated for prepared Libda cement samples. Environmental problems have been taken into consideration as a serious situation in modern construction. The reuse and recycling of waste are seen as the only method of reducing the waste generated. However, applications continue to have many opportunities for improvement.